DETECTION AND INVESTIGATION OF ASPERGILLUS NIGER AND OCHRATOXIN A IN WALNUT AND PEANUT - & et al., Khalifa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted at the Department of Plant Protection-College of Agriculture-University of Baghdad during 2015 -2016. The objective of the study is to investigate the contamination of the fungus Aspergillus niger in the seeds of peanuts and walnuts from the Iraqi local markets and the ability of these isolates to produce ochratoxin A in artificial medium. Forty samples of peanuts and walnuts were collected from local markets of the governorates of Baghdad, Erbil, Sulaymaniyah , Anbar and Dyiala for isolation test of A. nigar. Results showed that A.niger was founded in the samples of walnuts from Erbil at percentage of 50% and 42.8% in the samples of peanuts from Baghdad ,and 40 % in peanuts from each Anbar and Dyiala, in addition to the fungus A.flavus at a rate of33.3 و 28.8 % in the walnuts from Erbil and Baghdad respectively and 30% و28.8% in the peanuts from Anbar and Baghdad respectively. Eleven isolates of fungus A.niger was tested against its ability to produce Ochratoxin A after grown in yeast and sucrose extract media and analyzed using thin layer chromatography (TLC) under UV light wave length of 365 nanometer, two isolates were identified (K,E) out of the A.niger fungus isolated from peanuts found to be able to produce Ochratoxin A at different rates, depending on the degree of the brightness of the spots compared with standard Toxin. Then the eleven isolates were identified by morphology characters and confirm by using specific primer NIG1and NIG2, all the isolates showed to be A.niger.